Decisions, decisions, decisions. A qualitative exploration of decision-making in performance support leaders - Wilson, P. J.; Roe, Gregory; Kiely, John (Frontiers in Sports and Active Living, 2025)
Despite the assumed importance of decision-making in competitive sport environments, little is known about how performance support leaders (PSLs) make decisions within their professional contexts. This study aimed to explore how PSLs in high-performance sport approach decision-making tasks and understand the factors that influence their decisions. Using a pragmatic philosophy, fifteen PSLs working in performance sport, working across a range of countries and sports, were interviewed using a rigorously developed semi-structured interview protocol. Thematic analysis identified three key themes: emotional intelligence competencies, experience, and organizational structuring. The PSLs placed significant importance on having the necessary emotional intelligence to self-regulate and work cooperatively with others and having the necessary experience to develop the context-specific knowledge and skills required to make effective decisions. PSLs also emphasised the value of collaborative approaches when making difficult decisions, and the need for an organisational structure enhancing and enabling decision-making through clear systems, processes, and departmental structures. PSLs referenced individual and group reflective practices as key promoters of learning from previously made decisions. However, most PSLs have not undertaken any formal decision-making training. Future research should evaluate how these factors' impact decision-making effectiveness in high-performance sport, through formal assessment of processes and outcomes. These findings may help establish a framework for developing evidence-based interventions serving to enhance decision-making effectiveness. The identified elements of emotional intelligence, experiential knowledge, and organizational structures represent critical leverage points that may enhance leadership practices and driving measurable improvements in performance outcomes.